The diversity of diurnal bird species on western slope of Mount Lawu, Java, Indonesia - A.A. KRISANTI; A. CHOIRUNNAFI; N.O. SEPTIANA; F.W. PRATAMA; F. AMELIA; A. MANJASWARI; P.A. SEPTININGTYAS; A.S. WATI; J.Y. SATRIA; I.L. ANI; T. WIBOWO; SUGIYARTO SUGIYARTO (Biodiversitas Journal of Biological Diversity, 2017)
Krisanti AA, Choirunnafi’ A, Septiana NO, Pratama FW, Amelia F, Manjaswari A, Septiningtyas PA, Wati AS, Satria JY, Ani IL, Wibowo T, Sugiyarto. 2017. The diversity of diurnal bird species on western slope of Mount Lawu, Java, Indonesia. Biodiversitas 18: 1077-1083. Mount Lawu is one of the highest inactive volcanoes in Java Island, Indonesia. Mount Lawu attracts people to cultivate its area for agriculture, but without proper management, the biodiversity in Mount Lawu is in threat. This research aimed to get information about diurnal bird diversity on the western slope of Mount Lawu which includes a forest area (FA), an agroforestry area (AA), and a residential area (RA). Data collection was performed through point count method in 5 to 6 point per sites within certain time intervals after dawn and before sunset. There were 61 bird species from 26 families with a total number of 1416 birds being observed. The diversity index of the western slope was 2.480, and the highest Hmax among observed areas was the forest area (3.714). Collocalia linchi (Di 37.92) and Pycnonotus aurigaster (Di 19.42) were very common almost in all observation areas. The most similar ecosystem was FA and AA (J 0.176), followed by AA and RA (J 0.24), and FA and RA (J 0.393). A better management of Mount Lawu is necessary to improve human and biodiversity wellness. The result of this study could be used as additional data to consider a stronger protection for the biodiversity in Mount Lawu.